2014
DOI: 10.12956/tjpd.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Main Risk Factors for Mortality After Cardiovascular Interventions in Newborns with Critical Congenital Heart Diseases

Abstract: Objective: It was aimed to define the main risk factors that affect mortality in infants with critical congenital heart disease (CHD). Material and Methods: We analyzed data from 105 infants with critical CHD underwent cardiovascular intervention at a tertiary neonatal intensive care unit (NICU) between September 2010 and January 2012. Demographic data, clinical findings (before and after intervention), type of intervention, and intervention risk score according to Risk Adjustment in Congenital Heart Surgery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Similarly, the disease with the highest mortality in our study was HLHS with a mortality rate of 81.9%. In our study, prematurity, SGA at birth, multiple pregnancy, maternal age at birth, CCHD group are the variables associated with survival in line with the literature [11,26,27,51]. In a study conducted in Brazil, prematurity, LBW, multiple pregnancy, comorbidity/congenital anomaly were associated with increased mortality in CCHD [11].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, the disease with the highest mortality in our study was HLHS with a mortality rate of 81.9%. In our study, prematurity, SGA at birth, multiple pregnancy, maternal age at birth, CCHD group are the variables associated with survival in line with the literature [11,26,27,51]. In a study conducted in Brazil, prematurity, LBW, multiple pregnancy, comorbidity/congenital anomaly were associated with increased mortality in CCHD [11].…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, although CCHD mortality has decreased gradually, the mortality of this group of diseases is still high [8,11,19,26,27,47]. Our study showed that while the mortality rate in the birth cohort was 16.6% in the neonatal period, it reached 31.6% and 33.7% at the end of the first and second years, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The mortality and survival of CCHD varies in various countries and regions around the world [ 8 , 10 , 14 17 , 19 , 20 , 30 ]. In a study conducted in Brazil between 2014 and 2016 evaluating survival and risk factors for death in newborns with critical and/or complex congenital heart disease in the neonatal period, the death rate was found to be 8.1 per 10,000 live births [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…58% of them died before surgery and 81% of preoperative deaths were during palliative care [ 30 ]. In a study in which 105 patients with CCHD who were followed up in a tertiary neonatal intensive care unit in Türkiye between 2010 and 2012, the mortality rate was 35.2% while in another tertiary center in 2017–2018, evaluating perioperative mortality in cases requiring intervention in the neonatal period, the overall mortality and the intervention mortality were found 27% and 22% respectively [ 19 , 20 ]. Several factors linked to CCHD mortality have been documented in prior studies.…”
Section: Discussionmentioning
confidence: 99%